Safe implementation of enhanced recovery after surgery protocol in transfemoral transcatheter aortic valve replacement. Issue 1 (2nd January 2021) - Szerlip, Molly; Tabachnick, Deborah; Hamandi, Mohanad; Caras, LuAnn; Lanfear, Allison T.; Squiers, John J.; Harrington, Katherine; Potluri, Srinivasa P.; DiMaio, J. Michael; Wooley, Jordan; Pollock, Benjamin; Schaffer, Justin M.; et al.
Abstract: Enhanced recovery after surgery (ERAS) protocols are gaining wide acceptance. We evaluated ERAS protocol implementation in transfemoral transcatheter aortic valve replacement (TAVR) patients. The ERAS protocol included (1) moderate sedation or general anesthesia with on-table extubation, (2) no pulmonary artery or urinary catheters, (3) arterial line removal within 4 hours, (4) no postoperative narcotics, (5) mobilization at 4 hours and ambulation within 8 hours, and (6) antihypertensive reinstitution without nodal blockers. Patients who received TAVR before and after ERAS implementation were compared (N = 121 and N = 368, respectively). The primary endpoint was total hospital length of stay (LOS). ERAS patients had a lower mean Society of Thoracic Surgeons predicted risk of mortality (6.7% vs 7.5%; P  = 0.04). Unadjusted analysis demonstrated that ERAS was associated with significantly decreased mean LOS (2.8 vs 4.0 days, P  <  0.001), decreased 30-day mortality (0.8% vs 5.0%; P  = 0.003), and increased discharge home (90.2% vs 79.3%, P  = 0.002) with no increase in 30-day readmission (11.1% vs 14.0%, P  = 0.39). After risk adjustment, ERAS patients had a 1.87-day shorter LOS ( P  = 0.001) and trended toward increased discharge home (odds ratio 1.76, P  = 0.078) without increased readmission (odds ratio 0.74, P  = 0.4). An ERAS protocol for TAVR is safe and is associated with shorter LOS without increased readmission.